Cardiorespiratory and metabolic adaptation during the swimming and cycling sectors of an Olympic triathlon - Gonzalez-Haro, C.; Gonzalez-De-Suso, J. M.; Diaz-Beitia, G.; Valle, J.; Padulles, J. M.; Drobnic, F. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of this study is to analyse the metabolic and cardiorespiratory adaptation in swimming and cycling, and the first transition of a simulated olympic triathlon at race pace intensity. Summary: Although triathlon is considered a continuous workout, it seems to be necessary to study the performance for every sector independently. Results showed that the relative intensities in the two sectors were different. The weight lowering and the possible dehydration did not decrease the triathlete economy during the cycling sector. The work accomplished during the swimming sector affected the cycling performance only during the first ten minutes of the sector. The intensity during the cycling sector was very near to the individual lactate threshold, at which intensity, theoretically, more lactate is being removed.